Mastering the Art of First Impressions: Tips to Write a Title, Abstract, and Keywords for a Medical Manuscript - Eapen, Kurian C.; Koikkara, Kirti Anna; Keshava, Shyamkumar Nidugala (Indian Journal of Radiology and Imaging, 2025)
Formulating the title and abstract of a manuscript is crucial to convey the essence of the research paper to the reader at a superficial glance. The title should be short and crisp, yet it should define critical information about the paper, such as the disease highlighted, any intervention studied, or the primary outcome. A structured abstract is required in most journals for an original research article, conveying a summary of the research. The keywords used in the title and abstract also play a vital role in the article's discoverability on various search engines, thereby increasing the overall reach and impact of the article. In this article, we highlight a few key points to consider while drafting the title and abstract of a medical manuscript.
Keywords: abstract; article; journal; keyword; manuscript; research; title